Coptisine enhances the sensitivity of chemoresistant breast cancer cells by inhibiting the function and expression of ABC transporters - Safaa Yehia Eid (Frontiers Media S.A., 2024)
BackgroundMultidrug resistance (MDR), mainly caused by ATP-binding cassette transporters (ABCTs) efflux, makes it difficult for many anticancer drugs to treat breast cancer (BC). Phytochemicals can reverse cancer's MDR by modifying ABC transporter expression and function, as well as working synergistically with anticancer drugs to target other molecules. The reversal effect of the isoquinoline alkaloid coptisine (COP) was assessed on four breast cell lines; Two sensitive MCF-7 cell lines with positive estrogen, androgen, progesterone, and glucocorticoid receptors, as well as MDB-MB-231 cells with negative estrogen, progesterone, and HER2 receptors, and two doxorubicin-resistant cell lines, MCF-7/ADR and MDB-MB-231/ADR.MethodsThe cytotoxicity of COP and its ability to improve doxorubicin (DOX) cytotoxicity were assessed using the MTT assay. The effectiveness of COP in reversing DOX resistance was evaluated by calculating resistance ratio (RR) values, combination index (CI), and isobologram (IB). The inhibitory effect of COP on ABCT efflux function in comparison to verapamil (VER) was evaluated by measuring the cellular accumulation of Rho123 using flow cytometry. The impact of COP, either alone or in combination with DOX, on the gene expression of ABCTs (P-gp/MDR1, BCRP, and MRP1) of investigated cell lines was assessed by RT-PCR.ResultsThe COP showed modest cytotoxicity on the examined cell lines. In MCF-7/ADR and MDA-MB-231/ADR cells, COP (31 μM) enhanced DOX cytotoxicity with CI (0.77 and 0.75), RR (2.58 and 3.33), and IB suggesting synergism. COP significantly inhibits ABCT function in resistant BC cell lines, increases Rho123 accumulation, and decreases efflux more than VER; 2.1 and 1.2-fold, respectively. The combination of COP and DOX had a strong inhibitory effect on ABCT function (3.1 and 3.9 times VER, P< 0.001) and downregulated the genes and protein expression of ABCT.ConclusionCOP reversed ABCT-mediated multidrug resistance in vitro, indicating its potential as a multidrug resistance-reversing agent in cancer chemotherapy.